2021
DOI: 10.1002/ctm2.468
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of exosomal miRNAs in diabetes mellitus

Abstract: Recent studies have closely associated exosomal microRNAs (miRNAs) with various human diseases, including diabetes mellitus (DM), which is a complex multifactorial metabolic disorder disease. In the diabetic condition, exosomal miR-NAs are taken up by recipient cells, where they exert their biological function and thereby modulate the progression of DM-associated complications, including diabetic retinopathy (DR), diabetic macrovascular complications (DMCs), diabetic nephropathy (DN), diabetic foot ulcer (DFU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 188 publications
1
74
0
Order By: Relevance
“…In 1987, Johnstone et al defined and named these small vesicles with membranebased structure as exosomes (9). Exosomes are a type of extracellular vesicles (EVs) that exist in almost all kinds of body fluids, e.g., saliva, urine, and amniotic fluid (10)(11)(12). These EVs, including exosomes, were once considered cell waste products, but several studies have revealed that they can carry various cellular gene products, such as proteins, and a series of metabolites, which can be transferred to recipient cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…In 1987, Johnstone et al defined and named these small vesicles with membranebased structure as exosomes (9). Exosomes are a type of extracellular vesicles (EVs) that exist in almost all kinds of body fluids, e.g., saliva, urine, and amniotic fluid (10)(11)(12). These EVs, including exosomes, were once considered cell waste products, but several studies have revealed that they can carry various cellular gene products, such as proteins, and a series of metabolites, which can be transferred to recipient cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods of vesicle extraction and isolation are limited to in their ability to isolate different subtypes of EVs. Therefore, the terms “EV,” “sEV,” and “exosome” are used interchangeably in some studies (He et al, 2021b ). This review focused on the function of exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional therapeutic drugs, exosomes carrying drugs are more likely to pass through the blood-brain barrier (BBB), which helps the drugs to reach the target tissue (Azarmi et al, 2020 ). Due to the prevalence and easy availability of exosomes in the organism, as well as their involvement in various biomodulatory effects, exosomes have been considered as potential biomarker candidates for the clinical diagnosis and prognosis of diseases (He et al, 2021b ). Over recent years, an increasing number of studies have explored the specific mechanisms of exosome involvement in brain disease (Soares Martins et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are extracellular vesicles that originate from the multivesicular bodies (MVBs) and are present in intercellular space or circulate in biological fluids ( Kalluri, 2016 ; Zhang and Yu, 2019 ; He et al, 2021a ). These vesicles can be internalized by neighboring cells or by remote receptor cells through fusion with the target cell membrane, thereby altering the behavior of the target cell ( Hessvik and Llorente, 2018 ; Gonda et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%